High-sensitivity troponin and incident dementia: more evidence of connected heart and brain health - Giannitsis, Evangelos; Frey, Norbert; Katus, Hugo (European heart journal, 2026)
This editorial refers to ‘High-sensitivity cardiac troponin I and risk of dementia: the 25 year longitudinal Whitehall II study’, by Y. Chen et al., https://doi.org/10.1093/eurheartj/ehaf834.In 2020, ∼55 million people were living globally with a diagnosis of dementia. Due to ageing and growing populations, this number is predicted to almost double every 20 years, eventually reaching 78 million in 2030 and 139 million in 2050.1 Common causes of dementia include Alzheimer’s disease, vascular dementia, dementia with Lewy bodies, fronto-temporal dementia, and Parkinson dementia.2 Often arteriosclerotic and small vessel disease contribute to cognitive impairment in these dementia phenotypes including in Alzheimer’s disease, and the most prevalent phenotype is mixed dementia. Prevention of cerebrovascular disease has lowered dementia cases by some 30%, resulting in 1.5-1.8 million fewer people with dementia in 2020.3 While chronological ageing and genetic predisposition such as variants in the apolipoprotein E (APOE) gene are non-modifiable, a growing body of evidence exists linking 14 potentially modifiable risk factors including hypercholesterolaemia and obesity to cognitive function decline.2 The same risk factors associated with dementia also contribute to cardiovascular (CV) morbidity and mortality.
Veröffentlicht: 12. Dezember 2025
Gesehen am 05.02.2026